Pattern of Energy and Protein Intake among Stunted Children Aged 3â5 Years in Jatinangor - Laurus, Geraldo; Fatimah, Siti Nur; Gurnida, Dida Akhmad (Althea Medical Journal, 2016)
Background: A childâs optimal growth can be indicated by many factors, among them is body height, therefore stunting is one of the evidences of undergrowth. Nutrition, on the other hand, is one of variables affecting growth. This study aimed to examine the nutrition intake, in the form of energy, carbohydrate, protein, and fat in stunted children aged 3â5 years in Jatinangor.Methods: This cross sectional study was carried out in September to October 2014 using the random sampling method. Dietary data from 70 stunted children aged 3â5 years in preâschool and kindegarten located in 9 urban areas in Jatinangor were collected through 3x24 Recall and Food Frequency Questionaire and analyzed.Results: Mean energy intake was 1113.6 kcal and mean carbohydrate intake was 137.4 grams. Mean protein intake was 38.4 gram and mean fat intake was 38.2 gram. Types of food highly consumed as the source of carbohydrate were white rice and biscuit, and as the source of protein were meatball, sausage, and egg. Highest consumed vegetables, fruits and snack were water spinach, cabbage, watermelon, banana, and milk respectively.Conclusions: Mean energy intake, mean carbohydrate intake, and mean fat intake are all below the recommended dietary allowance (RDA) 2013 with individual value of mean energy intake is below RDA 2013 for all subjects. Mean protein intake is slightly above RDA 2013. [AMJ.2016;3(3):364â 70]DOI: 10.15850/amj.v3n3.907Â